ANALISA VEGETASI PADA PENGELOLAAN HUTAN TRADISIONAL MASYARAKAT SUKU DAYAK TAMAMBALOH DAN IBAN DI WILAYAH REDD+ KPHP MODEL KAPUAS HULU - Budiwan, Arie; Fahrizal, .; Prayogo, Hari (Universitas Tanjungpura, 2018)
Regional Demontration Areas Reduction of Emission from Deforestation and Forest Degradation Plus (DA REDD +) KPHP Model Kapuas Hulu covering 3 subdistricts namely Embaloh Hilir, Embaloh Hulu and Batang Lupar was previously the area of Forest Management Rights (HPH) PT. Lanjak Deras Jaya Raya (PT. LDJR) which has been revoked by the Ministry of Forestry (Ministry of Forestry) in accordance with the Decree of the Minister of Forestry No. 214 / Menhut-II / 2012 dated May 3, 2012. Generally the location of the former forest concession rights will invite wild hackers to log in and manage the remaining stands. This will lead to forest degradation and deforestation. Now the area is managed by the Unit of Production Forest Management (KPHP) Kapuas Hulu Model. In addition to KPH, management support comes from the Forclime program aimed to reducing forest deforestation and degradation as well as improving community welfare, with proponents at KPHP Model Kapuas Hulu. This research is aimed to obtain stand potency data. The data source is a potential stand field data. Data collection techniques include observation, documentation study and inventory. Analyze method in the form of Vegetation Analysis important value index. Based on research on the species density and better diversity in the custom forest of Banua Ujung Village than in the Abau River Reservoir forests, but for better important value index in the Abau River Village. Comparison between Belansao Banua Ujung Village and Abau River Village Tembawang, for better density at Beleansao, but for better diversity in Tembawai, while important value index Â is relatively the same. The type of Durian has an important role in beleansao, as well as rubber in Tembawai. This is closely related to the consumption pattern of the Banua Ujung Village community who loves durian, but the Abau river community prefer the rubber to be tapped (rubberized) to increase the income of the community. However, it does not mean that all durians are consumed by Banua Ujung community, as some are sold to northern areas such as Badau and its surroundings.Keywords: iban, Tamambaloh, Vegetation Analysis